Pengaruh Kitosan Terhadap Jumlah Osteoklas dan Osteoblas Pada Tikus Galur Wistar Model Menopause - Nur, Muhammad (Journal of Islamic Medicine, 2017)
Chitosan is one of the most abundant and dispersed polymers in nature. It has a rapid healing effect for tissues and has an effect on bone remodeling. The purpose of this study was to prove that giving chitosan influenced the decrease of osteoclast number and increasing number of osteoblasts in female mice of wistar strain of ovariectomy menopause model.This study used a posttest only control group design. The total sample of 30 rats divided into three groups was randomized, osteoporosis was made with the menopausal model which was performed ovariectomy in the positive control group and the treatment group then in the treatment group was given chitosan extract of single dose of 45 mg / day via Nasogastric Tube (NGT). K1 was a negative control group (without ovariectomy and without chitosan), K2 was a positive control group (with no chitosan ovariectomy), K3 was the treatment group (ovariectomy and chitosan 45 mg / day).The results showed significant differences in the number of osteoblasts between K1 and K3, K2 with K3, and no significant differences were found in the K1 group with K2. While the number of osteoclasts showed that there were significant differences in K1 group with K2 and no significant difference was found in K1 group with K3, K2 with K3.Conclusions in this study showed that 45 mg / day of chitosan doses could significantly increase osteoblast counts in menopause female white rats and decrease the number of osteoclasts performed by ovariectomy with chitosan administration.